PENGGUNAAN MEDIA PAPAN PINTAR MATEMATIKA (PAPINKA) UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KPK DAN FPB SISWA KELAS V SD N 060912 MEDAN DENAI - Rosvi Rahmawati; Chairunnisa Amelia; Jamilah Farah Dhiba (STKIP Subang, 2024)
This research aims to determine how effective the use of the KPK and FPB mathematics smart board (PaPinKa) media is in mathematics learning material for determining the value of the Least Common Multiple (KPK) and the Greatest Common Factor (FPB). This research conducted classroom action research (PTK) in two cycles. Each cycle consists of planning, action, observation and reflection stages. The subjects of this research were 5th grade students at SD N 060912 Medan Denai. In this research, observation, tests, and documentation were used to collect data. The research results show student learning achievement both in the pre-action and first cycle. In the first cycle, they had an average score of 73 and a completion percentage of 80%; in the second cycle, they had an average score of 86 and a completion percentage of 90%. This shows that the use of Mathematics smart board media in KPK and FPB material is very effective in improving the understanding abilities of class V students. Class Vb students at SDN 060912 Medan Denai learn about the Greatest Common Factor (FPB) and the Least Common Multiple (KPK) during the odd semester of the year. lessons 2024/2025.